LOCAL BLOOD FLOW AND MOTOR ACTIVITY JEJUNUM IN PATIENTS WITH EXTENSIVE PERITONITIS - B. B. Kapustin; S. V. Starchikov; R. F. Akhmetov (Креативная хирургия и онкология, 2017)
Assessment of changes in local blood flow and motor activity of the jejunum in the early postoperative period  in patients with diffuse peritonitis helps to identify  intraabdominale complications and to clarify the indications for relaparotomy.